2023
DOI: 10.3390/polym15112544
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Dynamic Mechanical Properties of Polypropylene-Fiber-Reinforced Foamed Concrete at High Temperatures

Abstract: Polypropylene-fiber-reinforced foamed concrete (PPFRFC) is often used to reduce building structure weight and develop engineering material arresting systems (EMASs). This paper investigates the dynamic mechanical properties of PPFRFC with densities of 0.27 g/cm3, 0.38 g/cm3, and 0.46 g/cm3 at high temperatures and proposes a prediction model to characterize its behavior. To conduct the tests on the specimens over a wide range of strain rates (500 s−1~1300 s−1) and temperatures (25~600 °C), the conventional spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…The results were tabulated in Table 4 to understand the varying trend of the compressive strength due to the addition of polypropylene fibers. Researchers (15,16) revealed that, in order for the foamed concrete to be suitable for structural purposes, it must possess a compressive strength of at least 25 MPa after 28 days.…”
Section: Compressive Strength Of Concretementioning
confidence: 99%
“…The results were tabulated in Table 4 to understand the varying trend of the compressive strength due to the addition of polypropylene fibers. Researchers (15,16) revealed that, in order for the foamed concrete to be suitable for structural purposes, it must possess a compressive strength of at least 25 MPa after 28 days.…”
Section: Compressive Strength Of Concretementioning
confidence: 99%
“…One example of such building materials that are most efficient in terms of energy saving is cellular concrete [11][12][13][14]. A number of works are known in the study of industrial, fuel, and energy waste as components in the composition of cellular concrete [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%